Task-Based Learning (TBL) in EFL classroom: from theory to practice - Muhammad Badrus Sholeh; Kisman Salija; Sahril Nur (International Journal of Humanities and Innovation (IJHI), 2020)
Task-Based Learning (TBL) is one of the contemporary approaches, which has attracted a great deal of study in recent decades. It is a language education approach that offers students the opportunity to use authentic target language use by tasks. Task-Based Learning drives skill-based teaching and learning, engages students in the learning process, motivates and enhances student imagination. This paper focuses on some fundamental aspects of TBL in literature: (1) the task-based learning definition, (2) the task-based learning characteristics, (3) the task-based learning framework, (4) the task-based learning benefits, and (5) a proposed task-based learning practice for EFL learners. The paper gives useful suggestions to EFL teachers who have similar teaching strategies to help students meet such learning goals in their classrooms and continue positive TBL patterns in teaching and learning.